Relevance of indirect comparisons in the German early benefit assessment and in comparison to HTA processes in England, France and Scotland - Andrea Lebioda; David Gasche; Franz-Werner Dippel; Karlheinz Theobald; Stefan Plantör (Health Economics Review, 2014)
Early benefit assessment in Germany under the legislative framework of AMNOG (Arzneimittelmarktneuordnungsgesetz) requires direct comparisons of the new drug with appropriate comparators determined by the Federal Joint Committee (G-BA). In case no head-to-head studies are available for direct comparisons, the submission of indirect comparisons is permitted to assess the additional benefit of the new drug. However, the Institute for Quality and Efficiency in Health Care (IQWiG) states a clear preference for head-to-head trials and defines strict requirements for indirect comparisons to be considered in the benefit assessment. Similar requirements also exist in other countries with mandatory health technology assessments (HTA), like France, England and Scotland. Our evaluation shows that a comparison of the different HTA regarding indirect comparisons is difficult. Overall, external preconditions and methodological requirements are demanding and hardly to fulfill by pharmaceutical companies for implementation of indirect comparisons in early benefit assessment. The determination of the appropriate comparators, outcomes, patient subgroups and study choice are the main target within indirect comparisons for the future. To compare and assess submitted indirect comparisons it would be desirable that a transparent process was established, including the mandatory publication of HTA-reports within Europe and international guidelines, accepted by a large number of HTA-agencies.
Keywords: I18; 330; AMNOG; Early benefit assessment; HAS; Indirect comparison; IQWiG; NICE